Dissociation of Connectivity for Syntactic Irregularity and Perceptual Ambiguity in Musical Chord Stimuli - Kim, Chan Hee; Jin, Seung-Hyun; Kim, June Sic; Kim, Youn; Yi, Suk Won; Chung, Chun Kee (Frontiers in Neuroscience, 2021)
Musical syntax has been studied mainly in terms of “syntactic irregularity” in harmonic/melodic sequences. However, “perceptual ambiguity” referring to the uncertainty of judgement/classification of presented stimuli can in addition be involved in our musical stimuli using 3 different chord sequences. The present study addresses how “syntactic irregularity” and “perceptual ambiguity” on musical syntax are dissociated, in terms of effective connectivity between bilateral inferior frontal gyri (IFGs) and superior temporal gyri (STGs) by linearized time delayed mutual information (LTDMI). Three conditions were of 5-chord sequences with endings of dominant to tonic, dominant to submediant, and dominant to supertonic. The dominant to supertonic is most irregular, compared to the regular dominant to tonic. The dominant to submediant of the less irregular condition is the most ambiguous condition. In the LTDMI results, connectivity from the right to the left IFG (IFG-LTDMI) was enhanced for the most irregular condition, whereas that from the right to the left STG (STG-LTDMI) was enhanced for the most ambiguous condition (P = 0.024 in IFG-LTDMI, P < 0.001 in STG-LTDMI, false discovery rate corrected). Correct rate was negatively correlated with STG-LTDMI, further reflecting perceptual ambiguity (P = 0.026). We found for the first time that syntactic irregularity and perceptual ambiguity coexist in chord stimuli testing musical syntax, and that the two sprocesses are dissociated in interhemispheric connectivities in the IFG and STG, respectively.